Do the current EU audit committee legal framework impact positively in audit quality? - Monteiro, D.; Laureano, Raul M. S.; Gaio, C. (19th Workshop on Corporate Governance, 2022)
Considering the last European Union audit legal framework related with Public Audit Entities (PIE), we explore how audit committee characteristics and role impact in audit quality. Our sample is composed of the first 15 Member States (MS) PIE’s and the measure of audit quality was based on quality of financial information through earnings management. The intra-European discrepancies in the audit committees’ legal framework provides an excellent opportunity to better understand potential drivers of audit quality, so we studied the period before the audit reform (2009-2015) when these context was less harmonized. We found evidence of a negative impact in case of total independent audit committees. However, the requirement of a majority of independent members seems to be associated to audit quality. The assignment of the functions related to the appointment of external auditors and the assessment of their independence shows a significant and positive association with audit quality. Similarly there is also a positive impact in audit quality of the exigence of technical expertise in accounting and auditing matters of audit committee members, particularly when that members were designated by general meeting. These conclusions might have important implications for regulators and corporate nominating bodies concerning the promotion of audit committee effectiveness.